1991
DOI: 10.1055/s-2008-1042491
|View full text |Cite
|
Sign up to set email alerts
|

Hematogenous Calcaneal Osteomyelitis in Children

Abstract: Heel pain is a frequent complaint in children due to intensive school and leisure-time sports. Heel pain accompanied by inflammatory signs has to be considered as osteomyelitis until the opposite is proven. From 1980 to 1989, twenty children were treated for acute or subacute osteomyelitis of the calcaneus (OMC) at the Department of Pediatric Surgery of the Children's Hospital of Lucerne. The schema of investigation comprising laboratory work-up, x-rays, scintiscanning and aspiration of the focus makes quick a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 11 publications
0
19
0
3
Order By: Relevance
“…aureus has been found to be the most common bacterial agent in hematogenous calcaneal osteomyelitis in this and other studies (4,5,10,21). Although P. aeruginosa occurred in one patient in this study, it is usually found in calcaneal osteomyelitis from puncture wounds (3,7,11,14,17,20).…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…aureus has been found to be the most common bacterial agent in hematogenous calcaneal osteomyelitis in this and other studies (4,5,10,21). Although P. aeruginosa occurred in one patient in this study, it is usually found in calcaneal osteomyelitis from puncture wounds (3,7,11,14,17,20).…”
Section: Discussionmentioning
confidence: 48%
“…The calcaneus has a "metaphyseal equivalent" region that borders the apophysis that is susceptible to hematogenous infection, like in long bones (16). An association with trauma has been reported in a few cases of calcaneal osteomyelitis (10,15,20,21). In this study 5 patients had a history of antecedent trauma.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations